Pentingnya Mengadopsi Ketentuan Lembaga Pre-Trial Chamber Pada International Criminal Court Dalam Sistem Peradilan Pidana Indonesia - Rahman, Yogi Muhammad; Noviansyah, Redo (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
Law enforcement against international crimes has its own system that is different from the national law enforcement system, as discussed in the previous paper related to the investigation of international criminal cases, it shows that there are fundamental differences, such as the initial process of investigation and law enforcement officials to the judicial system. In this paper, the author will focus on the discussion of the mechanism for the preliminary examination (Pre-Trial) in the International Criminal Court and the pretrial mechanism in the Indonesian criminal justice system. This study uses a normative juridical approach, which is a research conducted using a statutory or written regulation approach. The results show that the pre-trial chamber institution as regulated in the 1998 Rome Statute is very important to be adopted by the Indonesian government in the draft Law Code. Criminal Events. This is considering the advantages of implementing the pre-trial chamber system as an effort to supervise the actions of investigators and public prosecutors in handling a case.Keywords: International Criminal Law, Law Enforcement, Pre-Trial